2017
DOI: 10.1007/s00345-017-2062-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retroperitoneal and transperitoneal robotic partial nephrectomy for Pentafecta perioperative and renal functional outcomes

Abstract: TRPN and RRPN have similar quality outcomes, though RRPN may offer modest benefit for operative time and have utility in posterior tumors. Association of increasing RENAL score and decreased baseline eGFR with lack of Pentafecta suggests dominant role of non-modifiable factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…These findings were comparable to results from prior studies and were because of the advantages of directly approaching the kidney without bowel mobilization in the retroperitoneal approach. 16,[22][23][24][25] RRPN was associated with benefits of shorter WIT ( p = 0.008) and lower EBL ( p = 0.003) in all patients, although no differences were seen in patients with ‡4 cm renal tumors. Shorter WIT and lower EBL could affect functional outcomes and are regarded as prominent factors in RPN.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These findings were comparable to results from prior studies and were because of the advantages of directly approaching the kidney without bowel mobilization in the retroperitoneal approach. 16,[22][23][24][25] RRPN was associated with benefits of shorter WIT ( p = 0.008) and lower EBL ( p = 0.003) in all patients, although no differences were seen in patients with ‡4 cm renal tumors. Shorter WIT and lower EBL could affect functional outcomes and are regarded as prominent factors in RPN.…”
Section: Discussionmentioning
confidence: 91%
“…A single study compared TRPN and RRPN by Pentafecta criteria, but found variations in surgical procedures owing to multiple surgeons operating in two different centers. 16 Trifecta criteria were generated by Hung and colleagues as WIT £25 minutes, negative surgical margins, and no urological complications. 18 Pentafecta criteria added >90% preservation of baseline eGFR and no upgrading of CKD stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Stroup and colleagues reported similar result of a shorter operative time using a retroperitoneal approach and better utility in posterior tumors. 13 Our study has several limitations. First, this study was retrospective in nature, was conducted at a single institution, and included a population of tertiary care patients.…”
Section: Discussionmentioning
confidence: 91%
“…The feasibility of a retroperitoneal approach in RAPN has been evaluated in several studies. 12,13 Choo and colleagues compared surgical outcomes between transperitoneal RAPN and retroperitoneal RAPN with matched-pair comparisons by nephrometry score and demonstrated that retroperitoneal RAPN had a shorter operative time, but perioperative results were generally equivalent to those of transperitoneal RAPN. 12 Stroup and colleagues reported similar result of a shorter operative time using a retroperitoneal approach and better utility in posterior tumors.…”
Section: Discussionmentioning
confidence: 99%